PEMBAGIAN HAK WARIS PADA PERKAWINAN POLIGAMI DALAM MASYARAKAT ADAT MINANGKABAU KECAMATAN MATUR KABUPATEN AGAM - Zuliantika, Ananda; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In Minangkabau indigenous peoples the search property of husbands dividing their inheritance rights under Islamic law both in monogamous marriages and polygamy. Basically polygamous marriage must have a lot of husband's injustice as the head of the household. The division of inheritance of Islamic law in Minangkabau adat is somewhat ambiguous as the understanding of Minangkabau indigenous people towards Islam is low. In the general community, especially Agam Regency, there are still many problems faced in terms of distribution of inheritance, then in writing will be discussed about the prerogative of inheritance rights in polygamy marriage in Minangkabau indigenous people. The purpose of writing this thesis, namely: First Knowing how to divide the heirs in polygamy marriage in Minangkabau indigenous people Matur Sub-district Agam regency, Second Knowing the obstacles in the issue of division of inheritance rights in polygamy marriage in Minangkabau indigenous people Matur sub-district Agam regency.This type of investigation can be categorized into a sociological juridical research type. Because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Matur sub-district, while the population and sample were all parties related to the problem studied in this research. Sources of data used, primary data, secondary data and tertiary data, data collection techniques in this study by observation, interview and literature study.From the results of the study concluded that the division of inheritance on the wife and children in polygamous marriage in Minangkabau indigenous people has not been fully done inheritance law of Islam. Distribution of inheritance in the form of deliberation with consensus with the whole family. The problem that arises in the distribution of inheritance to wives and children in polygamous marriages in Minangkabau indigenous peoples is that the nephew / nephew is included in the heirs who are entitled to the heirs' private property. It is not in accordance with the division of inheritance in accordance with the Islamic inheritance law which prioritizes the distribution of inheritance to the wife or children of the testator as regulated in the Quran Sura Annisa. If a dispute arises between the two, the standard is perfect, that is, the law of inheritance of Islami.Keywords: Inheritance - Polygamy - Islamic Heritage - Minangkabau